An investigation into the local and traditional knowledge of the Saugeen Ojibway Nation regarding the status of ciscoes (Coregonus spp.) in Lake Huron - Duncan, Alexander T. (My University, 2020)
The ciscoes (Coregonus spp.) of Lake Huron are a poorly understood group of fish that have experienced declines in population numbers and a collapse of their ecological communities. Ciscoes are culturally and socio-economically important to the people of the Saugeen Ojibway Nation (SON), who have harvested them for food and commerce for generations. The decline in cisco populations has had significant impacts on the SON’s economy and traditional food availability, a key pillar of Indigenous food security. A community-based investigation SON fish harvesters’ Indigenous ecological knowledge (IEK) was conducted to address concerns about the cisco fishery and to determine if this knowledge can inform fisheries governance and socialecological relationships with ciscoes in Lake Huron. Sixteen semi-structured mapping interviews were held with past and current SON fish harvesters. Their IEK represented unique contributions that account for social and ecological perspectives. Two groups of ciscoes were identified, lake herring (Coregonus artedi) and chub (Coregonus spp.). The former is an important traditional food fish while the latter was a significant component of the SON fishery from the 1990s until the 2000s. A practical application of this IEK was successful cisco-specific sampling that was conducted in 2019. The results reveal that IEK has the potential to inform governance by identifying meta-level governance elements and the application of a two-eyed seeing approach. The IEK of the SON and their connection to these fish has been altered by numerous anthropogenic and ecological factors, but their legacy lives on.
Keywords: Ciscoes; Indigenous ecological knowledge; Saugeen Ojibway Nation (fishery); Fisheries governance and management